(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The ancient civilizations can provide some luminous clues for understanding the spiritual and psychological origins of human society and culture. In this quest, Vedic society and culture of ancient India can be a fertile source of insight, because it was built, guided and shaped by spiritual seers and thinkers who had a deep insight into the spiritual and psychological dimensions of life. During the late Vedic period with the emergence of agriculture as the dominant economic activity, the concept of cultural landscapes such as sacred forests and groves, sacred corridors, and a variety of ethno forestry practices evolved which continued into the post-Vedic period. The Himalayas since Vedic times also have been home for an array of medicinal plants and other resources.During the last two decades, some eccentric attempts have been made to identify the Indus Civilization with the Rig Vedic culture. Their conclusions are based on wrong assumptions claiming that (1) the Harappan sites have recently yielded the evidence of fire altars, sacrificial pits and true horse, so well-known to the Rig Veda, (2) that the Rig Vedic Saraswati was a mighty perennial river system parallel to the Indus and was the nucleus of Indus Civilization, (3) that the date of the Rig Veda goes back to the third millennium BC, the era of the Indus Civilization before the desertion of Kalibangan around 1900 BC and (4) that the Rig Vedic Aryans knew fortified cities, sea trade and state- based society. The protagonists of the thesis are selective in using only a fragment of the Vedic literature and comparing it with untested archaeological evidence. Their interpretation of the Rig Veda is based on distorted understanding of myths and metaphors of the ritual text.